FGF-21: THE HOMEOSTASIS GUARDIAN. A NEW OPTIMISM FOR OBESITY? - Gianni Yosephine; Anna Meiliana; Melisa I. Barliana (Farmaka, 2020)
The prevalence of obesity is increasing worldwide. Current obesity treatment is not suitable for all patients, hence the novel treatment are needed. Fibroblast Growth Factor 21 (FGF21) is a protein that consisting 210 amino acids. This protein is predominantly produced by the liver. In contrast to other FGF family members, FGF21 has a metabolic effect compared to cell proliferation and differentiation. It appears to be prospect treatment for metabolic syndrome, including obesity. Studies on FGF21 continue to develop and it is found that this protein has a beneficial role in the metabolism of lipids as well as glucose in vitro and in vivo. Interestingly, this protein also has the ability in energy homeostasis and has recently emerged as an intriguing therapeutic agent for obesity care. Because of its role as energy homeostasis, this protein can increase under certain conditions for example when fasting or on the ketogenic diet. Recombinant FGF21 administration in mice has been shown to reduce lipid levels. Assembling evidence from animal studies indicates that FGF21 is a potent metabolic regulator with many beneficial effects on obesity, even though the underlying mechanism of this effect is not fully understood. In the future it has potential to use FGF21 as treatment for obesity in human.